The history of sanitation in Brazil - Igor Luz Gonçalves; Caline Cecília Oliveira Leite; Débora da Silva Morais; Jhonata Soares dos Santos; Heitor de Sousa Pantarotto; Celso Oviedo da Silva Lopes; Glauber da Rocha Medeiros; Marcos Gabriel Carneiro da Silva; Tainan Rodrigues Corrêa; Juliana Mitie Isayama Asano; Marília de Oliveira Felten; Barbara Aiala Silva; et al. (Discover Water)
Abstract This study delves into the historical evolution of sanitation in Brazil, emphasizing how urban challenges and the advancement of hydrological concepts have shaped its development, leaving a profound legacy. While traditional sanitation principles are addressed, the study highlights a gap in understanding the origins of sanitary practices and their connections to urbanization and social needs, particularly those related to water management. By tracing this history, the research fosters critical reflection on current technologies, emphasizing the importance of contextualizing present-day solutions within their historical and social frameworks. In the Brazilian context, the study provides a comprehensive overview of sanitation development, from pre-colonial practices to modern advancements. Special attention is given to the evolution of concepts, infrastructure, legislation, and socioeconomic initiatives, offering a nuanced perspective on the interplay between policy, technology, and public health. The analysis focuses on the past 35 years, identifying key achievements, persistent disparities, and areas requiring further investment and innovation to ensure equitable and sustainable sanitation access. This exploration underscores the critical role of historical awareness in addressing policymakers and practitioners seeking to enhance water management and public health outcomes.